Pengembangan UI/UX Aplikasi Pinjam MIPA dengan Pendekatan Design Thinking - I Nyoman Suryadana; I Gede Santi Astawa (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2026)
This study presents the design and development of the Pinjam MIPA application as a digital system to support inventory management and borrowing activities among student organizations at the Faculty of Mathematics and Natural Sciences, Udayana University. The current manual process for borrowing often leads to data loss, unstructured schedules, and limited monitoring of inventory items. By applying the design thinking methodology, which consists of the empathize, define, ideate, prototype, and test stages, a user-centered solution was created to address these challenges. The application includes features such as digital inventory tracking, structured borrowing procedures, scheduling, and historical transaction records.. Usability testing with the System Usability Scale method produced an average score of 80.75, categorized as excellent, indicating that the application meets user expectations for ease of use and functionality. This work demonstrates that a design thinking approach can effectively improve efficiency, transparency, and accuracy in managing the lending of goods among student organizations. Future development may enhance notification features and real-time monitoring to further improve the system.